Valorization of a Bio-Stabilized Municipal Solid Waste Amendment for Faba Bean (Vicia faba L.) Fertilization - Sara Martinez; Sara Sánchez-Moreno; Jose Luis Gabriel; Cristina Álvarez; Maria del Mar Delgado (Agriculture, 2021)
The valorization of municipal solid waste (MSW) can serve as an organic amendment in agriculture while reducing solid waste accumulation in the environment. This research aimed to evaluate the valorization of a bio-stabilized MSW amendment for the production of faba bean (Vicia faba L.) crop. For this purpose, biomass production and growth, as well as, seed yield and seed components, seed nutrient accumulation, plant pigments, soil properties, and microorganisms were evaluated in comparison with faba bean mineral fertilization in a greenhouse experiment. The results demonstrated that the bio-stabilized MSW amendment achieved similar biomass production, plant growth, seed yield, nitrogen and protein content, and pigment content as the mineral fertilization treatment. On the other hand, the organic fertilization did not exhibit significant effects on the yield components number of pods per plant, and number of seeds per pod, and nutrient accumulation in seeds with respect to mineral and control treatments in both soils. Sandy and clay soil properties were improved in the organic treatments in comparison with the control soils by increasing soil organic carbon, nitrogen, and other soil nutrients, and providing a suitable pH for faba bean growth. Additionally, biological activity was favored by applying this source of organic fertilizer, enriching the nematode community. Reusing bio-stabilized MSW for agronomical purposes can add value to this waste product, serving as an effective alternative to mineral fertilizers in faba bean cultivation.